2014
DOI: 10.2340/00015555-2289
|View full text |Cite
|
Sign up to set email alerts
|

Serological Response to Treatment of Syphilis with Doxycycline Compared with Penicillin in HIV-Infected Individuals

Abstract: Serological response to treatment of syphilis with orally administered doxycycline or intramuscularly administered penicillin was assessed in patients with concurrent HIV. All HIV-infected individuals diagnosed with syphilis attending 3 hospitals in Copenhagen, Denmark were included. Odds ratios (ORs) with 95% confidence intervals (CI) associated with serological outcome were modelled using propensity-score-adjusted logistic regression analysis. In total, 202 cases were treated with doxycycline or intramuscula… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
16
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(17 citation statements)
references
References 30 publications
0
16
0
1
Order By: Relevance
“…Non‐penicillin antibiotics have been evaluated. These include tetracyclines (doxycycline is the preferred tetracycline with good penetration into the CSF) and macrolides, taken orally 99–103 . Doxycycline has been evaluated more than any other non‐penicillin antibiotics but all studies have been observational and retrospective 100–103 .…”
Section: General Remarks8792–97mentioning
confidence: 99%
See 2 more Smart Citations
“…Non‐penicillin antibiotics have been evaluated. These include tetracyclines (doxycycline is the preferred tetracycline with good penetration into the CSF) and macrolides, taken orally 99–103 . Doxycycline has been evaluated more than any other non‐penicillin antibiotics but all studies have been observational and retrospective 100–103 .…”
Section: General Remarks8792–97mentioning
confidence: 99%
“…These include tetracyclines (doxycycline is the preferred tetracycline with good penetration into the CSF) and macrolides, taken orally 99–103 . Doxycycline has been evaluated more than any other non‐penicillin antibiotics but all studies have been observational and retrospective 100–103 . Newer anti‐treponemal antibiotics include the intramuscular or intravenous extended‐spectrum cephalosporin (ESC) ceftriaxone 103–106 .…”
Section: General Remarks8792–97mentioning
confidence: 99%
See 1 more Smart Citation
“…Our study revealed that 81% achieved seroreversion after 12 months of treatment. One study indicated that nearly 70% of the latent syphilis cases with HIV coinfection achieved seroreversion [ 56 ]. Evaluating treatment effectiveness with the adequacy of serological responses showed a non-significant difference between BPG and DOXY, suggesting that DOXY can be used alternatively.…”
Section: Discussionmentioning
confidence: 99%
“…(2016) melakukan evaluasi klinis dan serologis pasien sifilis pada berbagai stadium dan menyimpulkan bahwa doxycycline dapat digunakan sebagai alternatif terapi yang efisien pada populasi dengan infeksi HIV. 12 Pada laporan kasus ini akan dibahas suatu kasus koinfeksi sifilis dan HIV pada seorang laki-laki homoseksual, dengan tujuan untuk memperdalam wawasan tentang penegakkan diagnosis dan manajemen terapi yang dapat diaplikasikan pada kasus serupa di poliklinik kulit dan kelamin RSUD Dr. Moewardi Surakarta.…”
unclassified